Comparison of fecal bacteriome of diarrhoeic and non-diarrhoeic calves revealed diversified community structures - Zebunnahar Yasmin; Mohammad Alamgir Hossain; Sharmin Chowdhury; Md. Habib Ullah Masum; Md. Shaminur Rahman; M. Nazmul Hoque; AMAM. Zonaed Siddiki (The Microbe)
The maintenance of healthy gut microbiota is of utmost significance when it comes to combating gastrointestinal disorders like diarrhoea. This study was designed to unveil the gut bacteriome signature and diversity by analyzing five diarrhoeic (DF) and five non-diarrhoeic feces (NDF) samples obtained from 10 individual calves through 16S rRNA (V4 region) gene-based amplicon sequencing. Our findings revealed substantial taxonomic variability between DF and NDF (p = 0.0127), indicated by their higher degree of shared microbiota. Among the identified genera, Gallibacterium and Veillonella were the major bacterial genera detected in the gut of calves, with marked discrepancies in their relative abundances in DF and NDF. We successfully identified 44 genera, including Sedimentibacter, Lonepinella, Sulfurospirillum, Haemophilus, and Enterobacter. which are linked to calf diarrhoea. The DF and NDF included 264 distinct bacterial species, of which 43.56 % were shared between sample categories, and 38.63 % and 17.80 % were found solely in DF and NDF, respectively. Moreover, Gallibacterium salpingitidis (43.37 %) was the most prevalent species in DF samples, followed by Gallibacterium anatis (17.56 %). In contrast, Veillonella magna (19.21 %) had the highest prevalence in NDF samples, followed by Bacteroides sp. (18.00 %). The findings suggested that diarrhoea affects the gut bacteriome in calves, with evidence for the existence of both unique and shared bacteriomes with pathogenic implications in the gut of calves. We expect that upcoming innovations will pave the way for personalized, microbiota-centered therapies, presenting hopeful approaches to influence microbial populations for better health results effectively.